2014
DOI: 10.1007/s00148-014-0519-7
|View full text |Cite
|
Sign up to set email alerts
|

Investing in children’s education: are Muslim immigrants different?

Abstract: Using a unique data set on immigrants living in France in 2003, we investigate whether Muslims invest differently in their children's education compared to non-Muslims. In particular, we want to assess whether educational inequalities between the children of Muslim and non-Muslim immigrants stem from differences between or within families. After controlling for a broad set of individual and household characteristics, we find no difference in education between children of different religions. However, we do fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The authors argue that a major goal of terrorist attacks is to induce a backlash against Muslims to radicalize moderate supporters who live in the same country as the perpetrators. 10 However, despite the growing economic literature on the integration of Muslim immigrants in western societies (e.g., Adida et al 2014;Arai et al 2011;Battu and Zenou 2010;Bisin et al 2008;Manning 2011, 2013;Manning and Roy 2010;Mitrut and Wolff 2014), no studies have used a panel structure to estimate changes in the integration attitudes of Muslim immigrants over time while accounting for unobserved heterogeneity. Therefore, there is no evidence which groups of individuals are most affected in terms of their perceived integration.…”
Section: Related Literaturementioning
confidence: 99%
“…The authors argue that a major goal of terrorist attacks is to induce a backlash against Muslims to radicalize moderate supporters who live in the same country as the perpetrators. 10 However, despite the growing economic literature on the integration of Muslim immigrants in western societies (e.g., Adida et al 2014;Arai et al 2011;Battu and Zenou 2010;Bisin et al 2008;Manning 2011, 2013;Manning and Roy 2010;Mitrut and Wolff 2014), no studies have used a panel structure to estimate changes in the integration attitudes of Muslim immigrants over time while accounting for unobserved heterogeneity. Therefore, there is no evidence which groups of individuals are most affected in terms of their perceived integration.…”
Section: Related Literaturementioning
confidence: 99%
“…Regarding educational attainment, some US research shows that Asians outperform other groups, while Hispanic students do less well compared to Asians and non-Hispanic Whites (Arias 1986;Hirschman and Wong 1986;Lee and Rong 1988). Using data on immigrants living in France, Mitrut and Wolff (2014) find no difference in the education of children of Muslim and nonMuslim immigrants, but observe more within-family inequality in children's educational achievements among Muslims relative to non-Muslims.…”
Section: Introductionmentioning
confidence: 91%
“…For instance, it has been found that Muslims are less likely to be employed than non‐Muslims in western Europe, while individual‐level factors explain less than half of the Muslim employment gap (Connor & Koenig, ). Studies also have shown that Muslim immigrants differ from natives and other immigrant groups in the expression of their religiosity, and their attitudes towards women and girls (De Hoon & Van Tubergen, ; Mitrut & Wolff, ; Adida et al , ). The recent events and violence in Europe and the USA have raised doubts and worries about the ability and willingness of Muslim immigrants and their offspring to integrate into Western society.…”
Section: Related Literaturementioning
confidence: 99%